2009
DOI: 10.1159/000218521
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Acute Stress Disorder and Posttraumatic Stress Disorder after Motor Vehicle Accidents

Abstract: Background: Since traffic accidents are more common in developing countries than in developed countries, we aimed to investigate the association of several factors with the development and persistence of posttraumatic stress disorder (PTSD) after traffic accidents. Sampling and Methods: In the study,95 participants with injuries from traffic accidents were evaluated at 4 different times: in the beginning, and after 3, 6 and 12 months. Results: During the first evaluation, 41.1% (39) of our participants had acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Posttraumatic stress disorder (PTSD) is another common and morbid health problem resulting from MVC [ 31 ], and the initial psychological response to MVC is an important indicator of PTSD risk following MVC [ 32 - 34 ]. PTSD is also known to be prevalent in approximately 1% of older adults [ 35 ], and advanced age may exacerbate symptoms of PTSD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) is another common and morbid health problem resulting from MVC [ 31 ], and the initial psychological response to MVC is an important indicator of PTSD risk following MVC [ 32 - 34 ]. PTSD is also known to be prevalent in approximately 1% of older adults [ 35 ], and advanced age may exacerbate symptoms of PTSD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial share of studies that investigated prevalence rates and predictors of PTSD following injury addressed certain injury subgroups, such as victims of motor vehicle accidents [4-7], burn victims [8-10] or patients who required admission to hospital or the Intensive Care Unit [3,11-15]. Those previous studies were mainly conducted in clinical patient populations and were therefore restricted to accidents and injuries at the higher end of the severity spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Data from WHO demonstrated that 20 to 50 million people are injured or disabled in road collisions over the course of one year [2]. These accidents are frequently followed by PTSD at about six months in 8.5–23.1% of victims [3,4]. However, many victims do not develop the symptoms that qualify them for the diagnosis of PTSD.…”
Section: Introductionmentioning
confidence: 99%